2016
DOI: 10.1159/000445617
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Expression Profile of Circular RNAs in Heart Tissue of Mice with Myocardial Infarction-Induced Heart Failure

Abstract: Background/Aims: Myocardial infarction (MI) is a serious complication of atherosclerosis associated with increasing mortality attributable to heart failure. This study is aimed to assess the global changes in and characteristics of the transcriptome of circular RNAs (circRNAs) in heart tissue during MI induced heart failure (HF). Methods: Using a post-myocardial infarction (MI) model of HF in mice, we applied microarray assay to examine the transcriptome of circRNAs deregulated in the heart during HF. We confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 31 publications
3
60
1
Order By: Relevance
“…In addition, cRNAs widely participate in the physiological/pathological processes involved in cancer [15]. Wu et al reported that the different expression patterns of circulatory cRNAs during heart failure (HF) suggest that cRNAs may actively respond to stress and thus serve as indicators for diagnosing HF [16]. As a type of cRNA, cANRIL can inhibit pre-ribosomal RNA processing mediated by exonuclease and prohibit ribosome biogenesis and the proliferation of cells, which may contribute to AS by inducing apoptosis in vascular SMCs [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cRNAs widely participate in the physiological/pathological processes involved in cancer [15]. Wu et al reported that the different expression patterns of circulatory cRNAs during heart failure (HF) suggest that cRNAs may actively respond to stress and thus serve as indicators for diagnosing HF [16]. As a type of cRNA, cANRIL can inhibit pre-ribosomal RNA processing mediated by exonuclease and prohibit ribosome biogenesis and the proliferation of cells, which may contribute to AS by inducing apoptosis in vascular SMCs [17].…”
Section: Introductionmentioning
confidence: 99%
“…This confers resistance to RNase R treatment, allowing circRNAs to be selectively enriched during sample processing and making them more suitable biomarkers than other types of RNA [7-9]. Studies demonstrated that circRNAs are involved in the development of several diseases, such as cancer [10-12], Alzheimer’s disease [13], major depressive disorder [14], atherosclerotic vascular disease [15], and pre-eclampsia [16]. Recent studies have found that circRNAs can bind to microRNAs (miRNAs) and act as “miRNA sponges” by sequestering target miRNAs and preventing them from regulating other endogenous target genes.…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are generally considerate as non-coding RNA, although Pamudurti et al found some specific circRNAs can also transcribed into proteins [7]. Increasing evidence reveals that circRNAs have key functions in regulating various physiological and pathological processes [8, 9]. It has been demonstrated that circRNAs could serve as competing endogenous RNAs (ceRNAs) to inhibit the activity of microRNAs (miRNAs) [10].…”
Section: Introductionmentioning
confidence: 99%